2019
DOI: 10.1177/1708538119892751
|View full text |Cite
|
Sign up to set email alerts
|

Primary conservative treatment for peritonitis-absent symptomatic isolated dissection of the superior mesenteric artery with severely compressed true lumen

Abstract: Objectives The purpose of this study was to evaluate the safety and efficacy of primary conservative treatment (PCT) for peritonitis-absent symptomatic spontaneous isolated dissection of the superior mesenteric artery (S-SIDSMA) with severely compressed true lumen. Methods From January 2013 to December 2018, PCT was used in 26 cases of peritonitis-absent S-SIDSMA with severely compressed true lumen in our center based on our previous proposed treatment algorithm for S-SIDSMA. The demographics, duration from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Furthermore, several authors have reported that even in cases where the true lumen is occluded, as in Yun's type III, the prognosis is often good with conservative treatment and type IIb recovers spontaneously because of the absorption of false lumen thrombus, and conservative treatment should be considered. 21,23,[26][27][28] In our case, the true lumen of the SMA dissection site was narrowed but not completely occluded, and the contrast effect of the SMA main trunk distal to the dissection site was maintained. If our cases had been type III, we would have performed revascularization during the initial surgery.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, several authors have reported that even in cases where the true lumen is occluded, as in Yun's type III, the prognosis is often good with conservative treatment and type IIb recovers spontaneously because of the absorption of false lumen thrombus, and conservative treatment should be considered. 21,23,[26][27][28] In our case, the true lumen of the SMA dissection site was narrowed but not completely occluded, and the contrast effect of the SMA main trunk distal to the dissection site was maintained. If our cases had been type III, we would have performed revascularization during the initial surgery.…”
Section: Discussionmentioning
confidence: 48%
“…[12][13][14][15] However, many authors have reported that conservative treatment alone led to successful recovery in patients accompanied by true lumen occlusion. 4,16 Studies have reported conflicting follow-up results; therefore, the association between the imaging features and prognosis of SISMAD remains unclear, particularly in patients with Yun's type III SISMAD (SISMAD accompanied by true lumen occlusion). 5,8 In this study, we summarize our findings and results of long-term follow-up of patients admitted to our hospital for management of Yun's type III SISMAD.…”
Section: Introductionmentioning
confidence: 99%
“…12-15 However, many authors have reported that conservative treatment alone led to successful recovery in patients accompanied by true lumen occlusion. 4,16…”
Section: Introductionmentioning
confidence: 99%